Characterization of Maternal Psychosocial Stress During Pregnancy: The Healthy Start Study - Satvinder K. Dhaliwal; Dana Dabelea; Angela E. Lee-Winn; Deborah H. Glueck; Greta Wilkening; Wei Perng (Mary Ann Liebert, 2022)
Objective: To capture multidimensional maternal psychosocial stress using responses from the Edinburgh Postnatal Depression Scale (EPDS) and Cohen's Perceived Stress Scale (PSS) administered during pregnancy, and to identify sociodemographic, biological, and health behavioral correlates of the stress domains. Methods: Using data from 1,079 pregnant women, we implemented principal component analysis on EPDS and PSS responses and retained factors based on the Scree plot and Eigenvalues >1. We then used linear regression to identify perinatal correlates of each domain. Results: We identified three stress domains: ?Feeling Overwhelmed,? ?Anhedonia,? and ?Lack of Control,? which accounted for 10.6% of variance in questionnaire responses. In multivariable analyses, household income ?$70,000 (??=?0.21 confidence interval [95% CI: 0.05?0.39]), primiparity (0.36 [0.02?0.71]), inadequate (0.21 [0.04?0.39]) or excessive gestational weight gain (0.27 [0.11?0.42]), and Healthy Eating Index (HEI) score ?57 (0.14 [0.00?0.28]) were associated with Feeling Overwhelmed. Older age (0.02 [0.00?0.03] per 1-year), Hispanic ethnicity (0.19 [0.00?0.38]), and HEI score ?57 (0.15 [0.02?0.28]) were associated with Anhedonia. Non-Hispanic Black race/ethnicity (0.37 [0.10?0.63]), not having graduated from college (0.16 [?0.02 to 0.35]), having a partner born outside the United States (0.17 [?0.02 to 0.37]), household size of ?5 persons (0.21 [?0.02 to 0.37]), receiving public assistance (0.18 [?0.02 to 0.37]), and prenatal smoking (0.32 [0.05?0.59]) were associated with Lack of Control. Conclusions: Three domains of maternal psychosocial stress during pregnancy (Feeling Overwhelmed, Anhedonia, and Lack of Control) were differentially related to sociodemographic, biological, and health behavioral characteristics that may be targets for interventions to ameliorate stress in pregnant women. Clinical Trial Registry: The Healthy Start study is registered as an observational study at clinicaltrials.gov (NCT #002273297).